1981
DOI: 10.1111/j.1348-0421.1981.tb00104.x
|View full text |Cite
|
Sign up to set email alerts
|

Pili Mediated Agglutination of Serratia marcescens in Human Urine

Abstract: Of 51 strains of Serratia marcescens isolated from patients with urinary or respiratory tract infections, 35 agglutinated in human urine. The agglutinating strains possessed numerous pili which were morphologically distinct from common pili or type I pili. The diameter of the pili was 3 nm and the average length was 0.3 um. Electron microscopic examination showed that 80% or more of the cells of the agglutinating strains and°to 8% of the cells of the nonagglutinating strains were piliated. When an agglutinatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…has also been reported (2,9). In a previous paper (2) we reported that a strain (US5) of S. marcescens possessing a distinctive type of fimbriae expressing mannose-sensitive (MS) hemagglutination is agglutinated by human urine. This agglutination of bacteria was found to be caused by the interaction of the fimbriae with the mucus present in human urine (6).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…has also been reported (2,9). In a previous paper (2) we reported that a strain (US5) of S. marcescens possessing a distinctive type of fimbriae expressing mannose-sensitive (MS) hemagglutination is agglutinated by human urine. This agglutination of bacteria was found to be caused by the interaction of the fimbriae with the mucus present in human urine (6).…”
mentioning
confidence: 99%
“…marcescens strain US5 was used as a fimbriated and strain US9 as a nonfimbriated strain. The characteristics of the fimbriae of US5 have been described in a previous paper (2,6,7,10). Strain US9, a clinical isolate, has no fimbrial structure or hemagglutination activity (2).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Serratia marcescens is an opportunistic organism that may cause nosocomial urinary and respiratory tract infections (2,7). The fimbriae of this species have been reported to be a colonization factor in such urinary tract infections (39).…”
mentioning
confidence: 99%